Dimethyl fumarate and mitochondrial physiology: implications for neurological disorders - de Oliveira, Marcos Roberto (Frontiers in Pharmacology, 2026)
Dimethyl fumarate (DMF; C6H8O4) is an ester of fumaric acid widely used in clinical practice for the treatment of relapsing forms of multiple sclerosis and plaque psoriasis. Beyond its established immunomodulatory actions, DMF is increasingly recognized as a small molecule capable of reshaping cellular redox homeostasis and mitochondrial physiology. Mitochondria are double-membrane organelles that integrate energy metabolism, calcium buffering, and apoptosis regulation, while also generating reactive oxygen species that function as signaling mediators. Given their central role in neuronal survival and function, mitochondrial integrity is a critical determinant of neuroprotection. The aim of this review is to discuss the mechanistic aspects by which DMF influences mitochondrial physiology in central nervous system (CNS) cells, based on evidence from experimental models and patient-derived samples. Data consistently show that DMF activates the Nrf2 pathway, leading to increased expression of antioxidant enzymes (e.g., NQO-1, HO-1) and induction of mitochondrial biogenesis markers (e.g., PGC-1α, NRF1, TFAM). In neurons and oligodendrocytes, DMF enhances respiratory function and limits apoptosis by modulating BCL-2 family proteins and suppressing cytochrome c release. Disease-relevant studies further demonstrate frataxin upregulation in Friedreich’s ataxia and reduction of mitochondrial reactive oxygen species in C9orf72-related models. Conversely, in microglia, T cells, and vascular cells, DMF may impair mitochondrial respiration or increase apoptosis, particularly under inflammatory stress, suggesting a context-dependent effect. In conclusion, DMF exerts multifaceted and cell type–specific actions on mitochondria. Understanding these mechanisms may guide optimized therapeutic strategies and the identification of biomarkers for precision use in neurological disorders.